The potential effect of different types of flaxseed (linum usitatissimum) extract on the cell viability of oral fibroblasts human cell line - Naziyah Shaaban, Sama; Mokhtar@Makhtar, Khairani Idah; Arief Ichwan, Solachuddin Jauhari; Mustafa Al-Ahmad, Basma Ezzat; Ashour, Abdelkader Elbadawy Abbas (2019)
Herbal medication and natural products has been successfully demonstrated to have general health beneficial effects. The bioactivities of flaxseed (linum usitatissimum) extract have been reported, as previous studies have shown that l. usitatissimum extract has many health and beneficial effects such as antimicrobial, anti-oxidant and anti-inflammatory effect. This study demonstrates and compares the effect of flaxseed extract in three different ethanol extract concentration on the viability of human oral fibroblast cells.